Men, Mobs, and Law : Anti-Lynching and Labor Defense in U.S. Radical History - Hill, Rebecca Nell, 1969- (Book collections on Project MUSE., 2008)
Compares the anti-lynching movement (epitomized the NAACP) to the movement in defense of labor activists (epitomized by the ACLU), and the rhetorical strategies they used to shape public opinion.